Gender equality in selected novels of Jane Austen: coping with anxiety to redefine home and gender roles - Naqashbandi, Bushra (2023)
The thesis is concerned with understanding the creation and evolution of gender equality in selected novels of Jane Austen. The characters’ lived experiences of home, anxiety due to the lived experience, defining and redefining home based on anxiety and their execution of gender roles is examined to understanding the process of creation of gender equality. A significant amount of research has been conducted on Austen’s creation of home and its meaning to her protagonists as well as the characters’ implementation of gender roles. Most of the studies focus on women from Austen’s major novels with relatively lesser studies analysing the meaning of home for Austen’s male protagonists or protagonists from her minor novels. Austen’s portrayal of home has been analysed mostly from sexual or social perspectives. Sources of anxiety in the lived experience of home of Austen’s protagonists have rarely been analysed in connection with the processes of defining home and interpreting gender roles. This research examines how coping with anxiety in the lived experience of home to define and/or redefine home and perception of gender roles creates gender equality between the protagonists in selected novels of Austen. A domestic lens is applied to analyse six characters from the major and minor mature works of Austen. The defense mechanisms of “isolation” and “undoing” defined in the Diagnostic and Statistical Manual of Mental Disorders by the American Psychological Association are used to investigate how the selected characters cope with anxiety arising from sources in the lived experience of home. The construct of Psychological Home by Sigmon, Whitcomb and Snyder is utilised to understand how the characters define home through associations with people, spaces and/or objects. The concepts of “doing gender” and “undoing gender” by Francine Deutsch are employed to study the characters’ implementation of gender roles. Finally, Janet Shibley Hyde’s Gender Similarities Hypothesis is applied to the selected texts to understand the creation and evolution of gender equality. The selected characters suffer from anxiety about losing their home which stems from tyrannical and/or indifferent treatment at the hands of family members, displacement and homelessness. The characters’ anxiety and experiences influence the manner in which they define home as well as their understanding of gender roles. They employ defense mechanisms to cope with their anxiety until they learn to control it by creating psychological homes or havens through their fluid implementation of gender roles. The fluid interpretation of gender roles highlights similarities between the sexes and creates equality between them.